3D free-standing hierarchical CuCo2O4 nanowire cathodes for rechargeable lithium–oxygen batteries. Issue 62 (19th July 2017) - Sun, Wang; Wang, Yan; Wu, Haitao; Wang, Zhenhua; Rooney, David; Sun, Kening
Abstract : Novel 3D free-standing carbon- and binder-free cathodes were prepared and efficiently improved the electrochemical performance of Li–O2 batteries. Abstract : A carbon and binder-free cathode for use in Li–O2 cells which is based on free-standing CuCo2 O4 nanowires supported on a nickel foam was synthesized by an efficient hydrothermal method. The resulting hierarchical porous and umbrella structures of the hybrid CuCo2 O4 @Ni foam cathodes present an excellent rate capability and cycle performance.